Consistent solitons in the plasma and optical fiber for complex Hirota-dynamical model - Ali, Karmina K.; Tarla, Sibel; Ali, Mohamed R.; Yusuf, Abdullahi; Yilmazer, Resat (Elsevier, 2023)
In this paper, the nonlinear complex Hirota-dynamical model is explored using the unified auxiliary equation method, which is the most powerful method for studying exact solutions to nonlinear models. This model is one of the important standards of the nonlinear Schrodinger equation in which the third derivative term represents the self-interaction in the high-frequency subsystem. Typically, in plasma, this term is isomorphic to the so known self-focusing effect. The aforementioned equation is crucial to plasma physics due to the agreements between the self-interaction at high frequency and the well-known self-focusing effect in plasma. Different structures of solutions are successfully investigated for this model. Consequently, we obtain some solutions like dark-bright, bright, dark, singular, periodic, trigonometric function, Jacobi elliptic function, and exponential solutions. We simulate the 2D, 3D, and counter plots of the constructed solutions by choosing the suitable values of the parameters involved.
Keywords: Soliton solutions; Nonlinear complex Hirota-dynamical model; Unified auxiliary equation method; Jacobi elliptic functions